Smart City: aspetti geomatici di un paradigma "fuzzy” - Fiduccia, Andrea (GEOmedia, 2013)
Il concetto di Smart City viene proposto con molte varianti non sempre tra loro coerenti. Ne sceglieremol'accezione che propone la possibilità di una migliore qualità della vita negli spazi urbani rimpiazzandone lacaotica complessità con innovazioni tecnologiche per realizzare i nostri progetti di lavoro e di vita. All'interno delparadigma ci concentreremo sugli specifici aspetti del segmento disciplinare della geomatica. Smart City: geomatics aspects of afuzzy paradigm The label smart city is still quite a fuzzyconcept and is used in ways that arenot always consistent. We endorsethe definition that "a city can be definedas ‘smart' when investments inhuman and social capital and traditional(transport) and modern (ICT)communication infrastructure fuelsustainable economic developmentand a high quality of life, with a wisemanagement of natural resources,through participatory governance”.Geomatics provides a set of conceptsand tools for the planningand management of Smart Cities(City Sensing,City Model, ProximalSensing, WIKI Sensing, etc). The IntegratedOperations Center (IOC)is the foundation using geographictechnologies to join Smart City withSafe City. Smart Grid Systems are away to make operational the urbansosteneability in the energy sector.Some Intergraph's technologies areused as examples of the contributionof geomatics in the implementationof Smart City paradigm.